To write the equation \( y - 3 = 2(x + 4) \) in standard form, we will first simplify it and then rearrange it.
-
Distribute on the right side: \[ y - 3 = 2x + 8 \]
-
Add 3 to both sides: \[ y = 2x + 11 \]
-
Now, we want to rearrange this into standard form \( Ax + By = C \). We will move \( 2x \) to the left: \[ -2x + y = 11 \]
-
To present the equation in the standard form with a positive \( x \) coefficient, we can multiply through by -1: \[ 2x - y = -11 \]
Now, rearranging gives: \[ 2x - y = -11 \] If we want to match it with the options provided, we rewrite it as: \[ 2x + (-y) = -11 \]
Now we can see that:
The solution choices presented were: A. \(-2x + y = 5\) B. \(-2x + y = 11\) C. \(2x - y = -11\) D. \(2x + y = 11\)
The correct answer is: C. \(2x - y = -11\)